Cutaneous sun damage and skin protection: a focus on FiltaClear. (2nd April 2019) - Paterson, Sue
Abstract : Phototoxicity (sunburn) and photosensitivity are the two most important forms of sunlight induced disease recognised by veterinary surgeons in the dog, cat and horse. Phototoxicity is mediated by UVB radiation and has a spectrum of presentations, ranging from sunburn to more severe actinic damage and squamous cell carcinoma. Phototoxicity is usually seen on white or non-pigmented skin especially where there is little hair covering and is recognised in all three species. Photosensitisation is most commonly seen in the horse and represents an abnormal reaction of the skin to light, caused by photodynamic agents in or on the skin. Sun avoidance and sun protection are important in all of the domestic species to prevent sunlight induced disease.